Implementasi Game Tebak Gambar Binatang Berbasis Android Sebagai Media Pembelajaran Anak Usia Dini - Prasetya, Renaldi Primaswara; Wahyuni, Febriana Santi; Rudhistiar, Deddy (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2024)
The increasingly rapid development of technology, especially mobile phone devices has targeted all groups, including young children aged 3 to 5 years, so like it or not,parents have to supervise their children. But in reality, technology cannot be avoided. As a parent, the most important thing right now is how to ensure that the mobile devices playing with children can be handled well and have a positive impact on their children, although supervision is still needed. Supervision of children who are already at school cannot be carried out continuously. At school, parents can only expect for the teachers as their second parents. Teachers as educators must be able to provide understanding to Kindergarten children, thus the use of cellphones can be used for positive things, one of which is by providing mobile game-based learning media. The problem is that there are only a few mobile applications in the form of games that provide simple learning media for Kindergarten children. Through this service, an Android-based educational game of animal picture guessing will be designed and developed as a learning medium for children aged 3-5 years. To determine the impact of implementing the application, implementation and testing were carried out, where the average System Usability Scale (SUS) score from 15 respondents was 88.33, and when referring to the usability scale value range it can be concluded that the animal picture guessing game that has been developed falls into the category acceptable or well accepted with a fairly significant impact category. Meanwhile the functionality also meets the needs of its users.